2018
DOI: 10.1002/brb3.878
|View full text |Cite
|
Sign up to set email alerts
|

Brain resting‐state networks in adolescents with high‐functioning autism: Analysis of spatial connectivity and temporal neurodynamics

Abstract: IntroductionAutism spectrum disorder (ASD) is mainly characterized by functional and communication impairments as well as restrictive and repetitive behavior. The leading hypothesis for the neural basis of autism postulates globally abnormal brain connectivity, which can be assessed using functional magnetic resonance imaging (fMRI). Even in the absence of a task, the brain exhibits a high degree of functional connectivity, known as intrinsic, or resting‐state, connectivity. Global default connectivity in indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…One study found fewer rapid transitions between brain networks in ASD compared to TD ( Watanabe and Rees, 2017 ). Studies by Bernas et al, 2018 and Damiani et al, 2018 have confirmed the abnormal temporal structure of the resting-state SN in ASD ( Bernas et al, 2018 ; Damiani et al, 2018 ). Although these studies have shed light on the temporal dynamics of brain network activity in ASD, they have been limited by the time resolution of the BOLD fMRI signal.…”
Section: Introductionmentioning
confidence: 87%
“…One study found fewer rapid transitions between brain networks in ASD compared to TD ( Watanabe and Rees, 2017 ). Studies by Bernas et al, 2018 and Damiani et al, 2018 have confirmed the abnormal temporal structure of the resting-state SN in ASD ( Bernas et al, 2018 ; Damiani et al, 2018 ). Although these studies have shed light on the temporal dynamics of brain network activity in ASD, they have been limited by the time resolution of the BOLD fMRI signal.…”
Section: Introductionmentioning
confidence: 87%
“…Independent component analysis (ICA) is a blind source separation technique that has been widely used to identify and quantify distribution area modes or spatial networks of related activities (Braden et al, 2017; Bernas et al, 2018; Bi et al, 2018). Additionally, it plays an important role in decomposing mixed data into independent components (ICs).…”
Section: Introductionmentioning
confidence: 99%
“…ICA is a data-driven analytical method to explore these independent component networks and their associated time series during the resting state. This method does not need a priori measurement signals and is independent of seed selection, which makes the resting-state analysis suitable and reproducible [6]. Prior studies discovered aberrant functional connectivity within intrinsic networks in the migraine-free period, such as visual network, default mode network and executive control network [7][8][9].…”
Section: Introductionmentioning
confidence: 99%